Surgery for patients with drug-resistant tuberculosis: report of 121 cases receiving community-based treatment in Lima, Peru. Issue 5 (23rd August 2006) - Somocurcio, Jose G; Sotomayor, Alfredo; Shin, Sonya; Portilla, Silvia; Valcarcel, Maria; Guerra, Dalia; Furin, Jennifer
Abstract : Background: While most patients with tuberculosis (TB) can be successfully treated using short-course medical chemotherapy, thoracic surgery is an important adjunctive strategy for many patients with drug-resistant disease. The need for physical, technical and financial resources presents a potential challenge to implementing surgery as a component of treatment for multidrug-resistant TB (MDR-TB) in resource-poor settings. However, a cohort of patients with severe MDR-TB in Lima, Peru underwent surgery as part of their treatment. Methods: 121 patients underwent pulmonary surgery for drug-resistant tuberculosis between May 1999 and January 2004. Surgery was performed by a team of thoracic surgeons under the Ministry of Health. Patient demographic data, clinical characteristics, surgical procedures and surgical outcomes were studied. Results: Most of the patients had failed multiple TB regimens and were resistant to a median of seven drugs. The median time of follow-up after surgery was 33 months. 79.3% of patients were culture-positive before surgery, and sustained culture-negative status among survivors was achieved in 74.8% of patients. 63% of those followed up for at least 6 months after surgery were either cured or probably cured. Postoperative complications, observed in 22.6% of patients, were associated with preoperative haemoptysis, vital capacity <50% and low forced expiratory volume in 1 s. Conclusions: This is one of the largest cohorts with MDR-TB to be treated with surgery, and the first from a resource-poor country. Although surgery is not often considered an option for patients in resource-poor settings, the findings of this study support the argument that adjunctive surgery should be considered an integral component of MDR-TB treatment programmes, even in poor countries such as Peru.